Upaya Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam (IPA) dengan Menerapkan Model Inquiry Training Berbantuan Media Audio Visual pada Kelas IV SDN 1 Narahan Tahun Pelajaran 2016/2017 - Sri Kartika Hayati; Diplan Diplan (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2019)
This study aims to: (1) Describe the activities of students in learning Natural Sciences (IPA) by applying the Inquiry Training model assisted by Audiovisual media in class IV students of SDN 1 Narahan 2016/2017 Academic Year, (2) Improving learning outcomes in Science Nature (IPA) fourth grade students of SDN 1 Narahan by applying the Inquiry Training learning model assisted by Audiovisual media. This type of research uses Classroom Action Research (CAR). Subjects in this study were all fourth-grade students of SDN 1 Narahan, totalling 14 students with a composition of 10 men and four women. Data collection techniques based on qualitative and quantitative in this study used a written test at the end of the learning process. The results showed that by applying the Inquiry Training learning model assisted with Audiovisual media (1) Activities of students in learning Natural Sciences (IPA) applying the Inquiry Training model supported by audiovisual media material Changes in the Physical Environment of the Earth in class IV SDN 1 Narahan Academic Year 2016/2017 is good. This can be seen from the assessment of observations by observers, namely, in the first cycle, the activities of students get an average score of 3.10 with a good category while in the second cycle the movement of students increases with an average rating of 3.80 and functional groups. (2) There is an increase in the learning outcomes of Natural Sciences (IPA) by applying the Inquiry Training learning model assisted by Audiovisual media in class IV students of SDN 1 Narahan in the 2016/2017 Academic Year. This can be seen in the Pre Test with an average value of 50 with a percentage of classical completeness of 14.28%, experiencing an increase in the first cycle with an average value of 65 with a portion of the artistic integrity of 64.28%. The results achieved by students in the second cycle for the average class value increased more than the previous period with an average value of 85 with a percentage of 100% classical completeness.